Light-attracted hawkmoths (Lepidoptera: Sphingidae) of Boracéia, municipality of Salesópolis, state of São Paulo, Brazil - Marcelo Duarte; Luciane Carlin; Gláucia Marconato (Check List, 2008)
The light-attracted hawkmoths (Lepidoptera: Sphingidae) of the Estação Biológica de Boracéia, municipality of Salesópolis, state of São Paulo, Brazil were sampled during a period of 64 years (1940-2004). A total of 2,064 individuals belonging to 3 subfamilies, 6 tribes, 23 genera and 75 species were identified. Macroglossinae was the most abundant and richest subfamily in the study area, being followed by Sphinginae and Smerinthinae. About 66 % of the sampled individuals were assorted to the macroglossine tribes Dilophonotini and Macroglossini. Dilophonotini (Macroglossinae) was the richest tribe with 26 species, followed by Sphingini (Sphinginae) with 18 species, Macroglossini (Macroglossinae) with 16 species, Ambulycini (Smerinthinae) and Philampelini (Macroglossinae) with seven species each one, and Acherontiini (Sphinginae) with only one species. Manduca Hübner (Sphinginae) and Xylophanes Hübner (Macroglossinae) were the dominant genera in number of species. Only Xylophanes thyelia thyelia (Linnaeus) and Adhemarius eurysthenes (R. Felder) were recorded year round.